THE EFFECT OF THE VARIED PACKAGING MATERIALS ON THE QUALITY OF SEAWEED JELLY CANDY (Gracilariasp.) STORED AT ROOM TEMPERATURE - Revi Susanti; N. Ira Sari; Suparmi Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThe objective of the research was to determine the effect of the different packaging materials on the quality of seaweed jelly candy during storage at room temperature. The method used was the experimental method and the design used was non factorial Randomized Block Design (RBD). The treatment conducted was packing the seaweed jelly candy with 2 varied packaging materials (HDPE and a combination of aluminum foil and HDPE). The results showed that the candy packed with HDPE obtained the score of appearance 6.62 (whole, neat and quite clear brownie), aroma 6.73 (slightly fresh typical of grass jelly candy), texture 6.64 (slightly chewy), taste 6.55 (slightly sweet and acidic). The candy contained moisture 17.64% and reducing sugar 16.97%. The value of folding test was 3.33 and the number of molds growth was 4.3 x 102 colonies/g). Meanwhile, the candy packed with combination of aluminum foil and HDPE obtained the score of appearance 6.32 (intact, neat and dark brown), aroma 7.34 (quite fresh typical of seaweed jelly candy), texture 6.70 (chewy typical of seaweed jelly candy), taste 6.95 (quite sweet and acidic). The candy contained moisture 17.48% and reducing sugar 20.37%. The value of folding test was 3.66 and the number of molds growth was 3.4 x 102 colonies/g). Thus, it can be concluded that aluminum foil combined with HDPE is the best packaging materials used for storing seaweed jelly candy for 28 days at room temperature.Keywords: Candy Jelly, Gracilaria sp., Packing, , Storage